1983
DOI: 10.1007/bf02906174
|View full text |Cite
|
Sign up to set email alerts
|

Pigment and acyl lipid composition of photosystem I and II vesicles and of photosynthetic mutants in barley

Abstract: The pigment and acyl lipid composition ofphotochemically active stroma lamellae and inside-out photosystem II vesicles have been investigated. Mechanical disruption followed by phase partitioning in an aqueous two phase system resulted in a clean separation of the photosystems. A qualitative and quantitative determination of the pigment content was achieved using reversed-phase high performance liquid chromatography. A single chromatographic separation provided adequate resolution of neoxanthin, violaxanthin, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

1983
1983
2010
2010

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 65 publications
0
19
1
Order By: Relevance
“…In vitro reconstitutions of LHCII have shown that xanthophylls are required for denatured apoproteins to be reconstituted with stable reassociation of chlorophyll molecules . This finding is supported by the observation that in general carotenoidless mutants are also depleted in LHCII (Henry et al, 1983;Michel et al, 1983). For the chlorophylllprotein ratio, reported values depended on the method used for LHCII purification: thus, Burke et al (1978) measured a value of 13 chlorophylls per polypeptide with preparation based on sucrose gradient centrifugation, whereas Thornbcr et al (1979) measured 6 for an SDS-PAGE preparation.…”
Section: The Major Chlorophyll Alb Protein Of Psii ( L Hcii)mentioning
confidence: 91%
“…In vitro reconstitutions of LHCII have shown that xanthophylls are required for denatured apoproteins to be reconstituted with stable reassociation of chlorophyll molecules . This finding is supported by the observation that in general carotenoidless mutants are also depleted in LHCII (Henry et al, 1983;Michel et al, 1983). For the chlorophylllprotein ratio, reported values depended on the method used for LHCII purification: thus, Burke et al (1978) measured a value of 13 chlorophylls per polypeptide with preparation based on sucrose gradient centrifugation, whereas Thornbcr et al (1979) measured 6 for an SDS-PAGE preparation.…”
Section: The Major Chlorophyll Alb Protein Of Psii ( L Hcii)mentioning
confidence: 91%
“…(Milford, Mass., USA) instrument (23). Both analytical and preparative separations were carried out by the use of a prepacked ktBondapack C-8 (l0 lain particle size) "Radial Pack Cartridge" (10 crux0.8 cm i.d.)…”
Section: Hplcmentioning
confidence: 99%
“…The French Press was operated at 3,600 lb. in-2 and the polymer concentration used was 5.80% (20). The inside-out photosystem II vesicles partitioned to the bottom phase, and were repartitioned with fresh upper phase until essentially all chlorophyll Figure 3: Polypeptide composition of inside-out photosystem II vesicles and of photosystem II membranes prepared with Triton X-100 and of the polypeptides released by Tris/NaCl washing or from thylakoids by sonication in the presence of NaC1.…”
Section: Preparation Of Inside-out Photosystem II Vesiclesmentioning
confidence: 99%
“…Inside-out photosystem II vesicles from barley ( Figure 3) had a similar composition although they were always contaminated to some extent with photosystem I components (20). Electron microscopy revealed that the preparation consisted of pairs of tightly appressed membrane sheets with only a limited volume at the edges (49).…”
Section: Characterization Of the Photosystem IImentioning
confidence: 99%